Caste and Gender in Contemporary India : Power, Privilege and Politics - Banerjee, Supurna; Ghosh, Nandini; Taylor and Francis (Boca Raton, FL : Routledge India, 2018)
This book explores the intersectional aspects of caste and gender in India that contribute to the multiple marginalities and oppressions of lower castes, with particular reference to Dalits, Muslims and women. It moves beyond the conventional accounts of experiences of women in unequal social and political relationships to examine how caste as a system and ideology shapes hegemonic masculinity and feminization of work, and thus contributes to the violence against women. The volume looks at their everyday lived realities within and across diverse social and political contexts families, education systems, labour, communities, political parties, power, social organisations, the politics of representation and the writing of the subaltern women. With a range of empirical work, it brings forth the complexities of identity politics and further analyses its limits in regional and historical frameworks. This book will be of interest to students, scholars and specialists in caste and gender studies, exclusion and discrimination studies, sociology and social anthropology, history and political science. It will also be useful to Dalit writers and people working in the development sector in India.
List of Tables -- Notes on Contributors -- Acknowledgements -- Glossary -- -- Introduction -- Interrogating Intersections, Understanding Identities ----Nandini Ghosh and Supurna Banerjee -- --Chapter 1 -- Thinking about Caste: An Autobiographical Journey----Uma Chakravarti -- Chapter 2 -- Negotiating with Patriarchy and Access to Higher Education----Vandana -- Chapter 3----Kaarigars, Karkhanas and the Art of Embroidery----Bidisha Dhar -- Chapter 4 -- Negotiating Gender: Caste and Disability Identities of Women in India----Nandini Ghosh -- Chapter 5 -- Caste Identity and Community Feast among Yadavs: An Interpretation----Devi Prasad -- Chapter 6 -- The Hindutva Politics of Uma Bharati: Challenges to Womens Movements----Nandita Banerjee Dhawan -- Chapter 7 -- Nationalism of Exclusion: Gaumata and her Unholy Sons----Supurna Banerjee -- Chapter 8 -- Chandalini-r Bibriti: Interrogating Caste and Gender in Contemporary Bengali Dalit Literature ----Praskanva Sinharay -- Chapter 9 -- Bamas Karukku: A Beaded String of Gender, Caste, Religion----Amrita Basu Roy Chowdhury -- Chapter 10 -- Caste-Gender Intersectionalities and the Curious Case of Child Nutrition: A Methodological Exposition----Simantini Mukhopadhyay and Achin Chakraborty -- --Index.
Includes bibliographical references and index.
Also available in print format.
Keywords: SOCIAL SCIENCE / Minority Studies; SOCIAL SCIENCE / Sociology / General; Disability, bodies, socio-cultural practices, sexuality, queer, activism, suicides, literary discourse, dalit, difference, untouchable, autobiography, religion, writing, education. subversion, dance, culture, choreography; gender, caste, intersectionality, grounded methodology, Hindutva, feminist, right wing, lower-caste, symbolism, purity, cow, identity, community, Reservation, Constitution, Scheduled Caste, Arunthiyar; Yadav, rituals, festival, exclusion, health care, inequality, NSSO, class, Inequity, methodological intersectionality, social power, quantitative approaches, labour, skill, relations of production, caste discourses; Caste -- India; Sex discrimination -- India; Caste; Sex discrimination; Social conditions; Electronic books